Spherical composite cerium oxide, polishing material and preparation method thereof
By controlling the molar ratio of ammonia water to ammonium source and adjusting the reaction conditions, the crystallinity and purity of spherical composite cerium oxide are improved, and the existing spherical cerium oxide is solved. The problem of low crystallinity and low purity in the production process is solved, and more efficient polishing performance is achieved.
Patent Information
- Application Number
- CN202510387889.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-31
AI Technical Summary
The existing spherical cerium oxide has problems of low crystallinity, low purity and surface defects during the production process, which affects its performance in polishing applications.
The preparation method of spherical composite cerium oxide is adopted. By combining cerium source, ammonia water, ammonium source, organic acid, nitric acid and water, the molar ratio of ammonia water to ammonia source is controlled between 1:0.2-0.4, and the reaction conditions are adjusted to promote the directional growth and uniform distribution of crystals, and to improve crystallinity and purity.
The spherical composite cerium oxide has high crystallinity (≥95%) and low impurity content (less than 1ppm), improving its application performance in semiconductor polishing and high-end optical polishing.
Smart Images

Figure CN119873872A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polishing materials, in particular to a spherical composite cerium oxide, a polishing material and a preparation method thereof. Background Art
[0002] Cerium oxide is a widely used rare earth metal oxide with excellent chemical stability, high temperature oxidation resistance and strong adsorption capacity. It is widely used in many fields such as catalysts, optical materials, batteries and polishing materials. As an important rare earth compound, cerium oxide has many special physical and chemical properties, especially its ability to convert between different oxidation states (Ce 4 ⁺ and Ce³⁺), which makes it show good catalytic performance in catalytic reactions. In addition, cerium oxide has strong thermal and chemical stability, and can still maintain its good performance under high temperature and high pressure environment, so it has become an important component of some high-performance materials.
[0003] Spherical cerium oxide is a specific form of cerium oxide, and its main feature is that its particles present a regular spherical structure. Compared with traditional particle forms, spherical cerium oxide has a more uniform particle distribution and better fluidity. Spherical cerium oxide not only has good polishing performance, but also can improve work efficiency to a certain extent and reduce the damage that may be caused to the semiconductor surface during the polishing process. These characteristics make spherical cerium oxide particularly widely used in the semiconductor industry, especially as a polishing material in the polishing process of semiconductor wafers, which plays a role in removing surface defects and improving surface flatness.
[0004] Semiconductor polishing is a crucial process in the semiconductor manufacturing process. Its purpose is to improve the flatness and finish of the wafer surface by removing tiny defects, impurity layers or oxide layers on the wafer surface. In this process, the selection of polishing materials is crucial because it is directly related to the quality of the polishing effect. Spherical cerium oxide is a commonly used polishing material and is widely used due to its excellent chemical and physical properties. First, cerium oxide has a moderate hardness and can effectively remove tiny defects on the surface of silicon wafers without excessively wearing the surface. Secondly, due to the spherical structure of the particles, spherical cerium oxide can be evenly distributed during the polishing process, providing a more uniform polishing force, thereby effectively reducing local over-polishing and surface unevenness. Furthermore, the particles of spherical cerium oxide have high surface activity and can form a good chemical reaction when in contact with the semiconductor surface, which helps to remove pollutants and improve surface quality.
[0005] However, existing spherical cerium oxide often faces problems of low crystallinity and purity during the production process, which affect its performance. First, spherical cerium oxide with low crystallinity has more amorphous phase regions, which usually lack the typical crystal structure of cerium oxide, making it impossible to perform optimally in some applications. In polishing applications, cerium oxide particles with low crystallinity often show poor stability and low polishing efficiency, which has a certain negative impact on its performance.
[0006] Secondly, the purity of existing spherical cerium oxide is usually unsatisfactory. Cerium oxide with low purity often contains more impurity elements, which may come from impurities in the raw materials or other ingredients added during the production process. The presence of impurities not only affects the catalytic performance of cerium oxide, but also may affect its effect as a polishing material. Certain impurities may react with the surface of the semiconductor during the polishing process, resulting in surface contamination or incomplete reaction, thereby affecting the polishing quality. In addition, the presence of impurities may also cause the chemical stability of spherical cerium oxide to decrease, resulting in failure or performance degradation during use.
[0007] Surface defects are another common problem in the production process of spherical cerium oxide. During the production process of spherical cerium oxide, especially during high-temperature calcination or other heat treatment processes, microcracks or other defects may occur on the surface of spherical cerium oxide due to the influence of factors such as atmosphere, temperature, and time. These defects will not only affect the overall strength of spherical cerium oxide, but also affect its application effect during the polishing process. The presence of surface defects may lead to a weakening of the bonding force between particles, thereby affecting the stability of the particles and further affecting the effect of the polishing process.
[0008] In general, the existing spherical cerium oxide has insufficient crystallinity, purity and surface quality, which limits its application in some high-precision fields. In order to meet the growing demand, improving the crystallinity, purity and surface quality of spherical cerium oxide has become the focus of research. Summary of the invention
[0009] The object of the present invention is to provide a spherical cerium oxide with good crystallinity, high purity and surface quality.
[0010] A first aspect of the present invention is: Provided is a spherical composite cerium oxide.
[0011] A second aspect of the present invention is: Provided is a method for preparing spherical composite cerium oxide.
[0012] The third aspect of the present invention is: Application of the spherical composite cerium oxide.
[0013] The invention also provides a method for polishing a semiconductor by using the spherical composite cerium oxide.
[0014] Specifically, the technical solution adopted according to the first aspect of the present invention is: A spherical composite cerium oxide, the preparation raw materials include the following components: Cerium source; ammonia; Ammonium source; Organic acids; nitric acid; water; The D50 of the spherical composite cerium oxide is 20-160nm; The molar ratio of the ammonia water to the ammonium source is 1:0.2-0.4.
[0015] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects: The spherical composite cerium oxide of the present invention has a regular shape, is uniformly concentrated, has good crystallinity, is high in purity and has few impurities, and can be widely used in the fields of semiconductor polishing, high-end optical polishing, cosmetics, etc.
[0016] Specifically, the addition of ammonia water and ammonium source in the raw materials can effectively coordinate the arrangement of cerium ions and other metal ions in the cerium source, promote the directional growth of crystals, and form particles with regular spherical morphology; the amount of ammonia water and ammonium source will adjust the reaction efficiency in the process of generating spherical composite cerium oxide, and the appropriate amount can promote the reaction to proceed fully, avoid morphological changes due to insufficient reaction, and avoid the increase of impurity content due to excessive reaction. The present invention controls the molar ratio of ammonia water to ammonium source to 1: 0.2-0.4, so that the crystallinity of spherical composite cerium oxide is ≥95 and the impurity content is less than 1ppm. In addition, the appropriate particle size D50 and the lower impurity content make the spherical composite cerium oxide more conducive to application in semiconductor polishing.
[0017] According to one embodiment of the present invention, the raw materials for preparing the spherical composite cerium oxide also include a praseodymium source and / or a neodymium source. Preferably, the raw materials for preparing the spherical composite cerium oxide also include a praseodymium source and a neodymium source. The praseodymium-neodymium rare earth metal ions of the praseodymium and / or neodymium source and the cerium ions in the cerium source are in the cerium oxide unit cell, which helps to stabilize the lattice structure, reduce impurities in the spherical composite cerium oxide, promote crystal growth, and thus improve crystallinity. Higher crystallinity helps to reduce defects. The reaction mechanism of ammonium source, praseodymium source and / or neodymium salt includes: the ammonium source, praseodymium source and / or neodymium salt (denoted as CeX, PrX and / or NdX) first reacts with organic acid (denoted as HR1) and inorganic acid (denoted as HR2) to generate R1CeR2, R1PrR2 and / or R1NdR2, and then R1CeR2, R1PrR2 and / or R1NdR2 react with ammonia water through sol-gel reaction to generate CeO2, PrO2 and / or NdO2, CO2, N2 and H2O, wherein CeO2, PrO2 and / or NdO2 are the components of spherical composite cerium oxide.
[0018] According to one embodiment of the present invention, the molar ratio of cerium ions, praseodymium ions and neodymium ions in the cerium source, the praseodymium source and the neodymium source is 100-1000000:1:1.
[0019] According to one embodiment of the present invention, the mass ratio of ammonia water to ammonium source is 1:0.21-0.4. The mass ratio of ammonia water to ammonium source can regulate the reaction rate, avoid the particles not being formed due to an overly intense reaction, and avoid the product yield falling below 50% due to a too slow reaction.
[0020] According to one embodiment of the present invention, the concentration of the ammonia water is 1% - 70% w / w.
[0021] According to one embodiment of the present invention, the D50 of the spherical composite cerium oxide is 90±10 nm.
[0022] According to one embodiment of the present invention, the cerium source includes at least one of cerium nitrate, cerium chloride, cerium sulfate and cerium carbonate.
[0023] According to one embodiment of the present invention, the ammonium source includes at least one of ammonium nitrate, ammonium phosphate, ammonium sulfate, ammonium acetate and ammonium chloride.
[0024] According to one embodiment of the present invention, the ammonium source is ammonium nitrate.
[0025] According to one embodiment of the present invention, the praseodymium source includes at least one of praseodymium nitrate, praseodymium chloride, praseodymium sulfate and praseodymium carbonate; the neodymium source includes at least one of neodymium nitrate, neodymium chloride, neodymium sulfate and neodymium carbonate.
[0026] According to one embodiment of the present invention, the organic acid includes at least one of formic acid, acetic acid, n-butyric acid, n-hexanoic acid and oxalic acid.
[0027] According to one embodiment of the present invention, the organic acid is acetic acid.
[0028] According to one embodiment of the present invention, the inorganic acid is nitric acid. Preferably, when the ammonium source is ammonium nitrate, the organic acid is acetic acid, and the inorganic acid is nitric acid, it can be ensured that the product impurities are less than 1 ppm.
[0029] Specifically, the technical solution adopted according to the second aspect of the present invention is: A method for preparing the spherical composite cerium oxide comprises the following steps: S1: mixing a cerium source with water, nitric acid, and an organic acid in sequence to obtain a first mixed solution; S2 adding ammonia water and an ammonium source to the first mixed solution, heating for reaction, and obtaining a second mixed solution; S3: adjusting the pH of the second mixed solution to be alkaline, and obtaining the spherical composite cerium oxide through a sol-gel reaction; In the step S2, the heating reaction temperature is 30°C-120°C, and the heating reaction time is 1-60 hours.
[0030] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects: The present invention controls the pH to be alkaline, thereby promoting the formation of spherical particles, making the reaction more controllable, and the nucleation and growth of the grains more uniform, ensuring the formation of regular nano-spherical composite cerium oxide; when using the sol-gel method, the cerium ions in the second mixed solution form a nano-scale gel network through a hydrolysis reaction, and are finally converted into uniform nanoparticles through dehydration and hydrolysis reactions during the sol-gel reaction. The sol-gel method can achieve relatively uniform particle growth and smaller grain size, which helps to control the shape and crystallinity of the material. Appropriate temperature and time can ensure that the spherical composite cerium oxide has high purity and few impurities. When the temperature is too low, the reaction cannot start. When the temperature is too high, impurities increase, and even the product cannot be formed.
[0031] According to one embodiment of the present invention, the mass ratio of the water in step S1 to the ammonia water and the ammonium source in step S2 is 50-100:4:2.
[0032] According to an embodiment of the present invention, in step S1, the volume ratio of nitric acid, organic acid and water is 2:1:100-280. The appropriate volume ratio of nitric acid, organic acid and water can ensure that the spherical composite cerium oxide has high purity and few impurities.
[0033] According to one embodiment of the present invention, in step S1, the mass ratio of the cerium source to water is 1: 100-20000. The mass ratio of the cerium source to water can also adjust the reaction rate. When the ratio of the ammonium source to water is too low, the product will not be formed. When the ratio of the ammonium source to water is too high, the reaction is too fast, and the product will not be able to form nanoparticles.
[0034] According to one embodiment of the present invention, in step S2, the temperature of the heating reaction is 30°C-85°C.
[0035] According to one embodiment of the present invention, in step S2, the temperature of the heating reaction is 85°C-120°C.
[0036] According to one embodiment of the present invention, in step S2, the heating reaction time is 1-120 hours.
[0037] According to one embodiment of the present invention, in step S2, the heating reaction time is 1-60 hours.
[0038] According to one embodiment of the present invention, in step S2, the heating reaction time is 60-120 hours.
[0039] According to one embodiment of the present invention, in step S3, the alkaline pH is 7.0-11.0. At other pH values, the particle shape of the spherical composite cerium oxide will change.
[0040] According to one embodiment of the present invention, the method for preparing the spherical composite cerium oxide further comprises the following steps: A1: mixing a cerium source with water, a praseodymium source and / or a neodymium source, nitric acid, and an organic acid in sequence to obtain a first mixed solution; A2 adds ammonia water and an ammonium source to the first mixed solution, and heats the mixture to react, thereby obtaining a second mixed solution; A3 adjusts the pH of the second mixed solution to be alkaline, and performs sol-gel reaction, concentration operation, and centrifugation operation to obtain the spherical composite cerium oxide; In the step A2, the heating reaction temperature is 30° C.-120° C., and the heating reaction time is 1-60 hours.
[0041] According to one embodiment of the present invention, step A3 further includes the following steps: after the second mixed solution undergoes a sol-gel reaction, it is concentrated by high-temperature distillation at 20°C - 160°C to obtain a sol, and the sol is concentrated and centrifuged to obtain the spherical composite cerium oxide.
[0042] According to one embodiment of the present invention, in the step A3, after the centrifugation operation, it also includes the steps of drying and deagglomeration.
[0043] According to one embodiment of the present invention, the concentration temperature of the concentration operation is 120°C - 180°C.
[0044] According to one embodiment of the present invention, after the concentration operation, the solid content of the obtained product is ≥60.0%.
[0045] According to one embodiment of the present invention, in the step A3, after the centrifugation operation, a drying operation is also included.
[0046] According to one embodiment of the present invention, the temperature of the drying operation is 300°C - 1100°C.
[0047] According to one embodiment of the present invention, the drying time of the drying operation is 2-12 hours.
[0048] Another aspect of the present invention provides a semiconductor polishing material, including the spherical cerium oxide composite material as described in the first embodiment. Since the application adopts all the technical solutions of the spherical cerium oxide composite material, it has at least all the beneficial effects brought by the technical solutions of the above embodiment.
[0049] Another aspect of the present invention provides a method for semiconductor polishing, comprising the following steps: fixing a wafer to be polished on a polishing disk, starting a polishing device, preparing the semiconductor polishing material into a polishing liquid and spraying the prepared polishing liquid onto the surface of the polishing pad for polishing.
[0050] According to one embodiment of the present invention, a method for semiconductor polishing comprises the following steps: The wafer to be polished is fixed on the polishing plate, the polishing equipment is started, and the semiconductor polishing material is sprayed onto the polishing pad and the surface of the wafer for polishing.
[0051] According to one embodiment of the present invention, the semiconductor polishing material is a polishing liquid, and the polishing liquid has the following components in parts by weight: Abrasive, 1.5-3.0 parts; Ultrapure water, 85.0-90.0 parts; Oxidant, 0.5-1 part; Complexing agent, 1.0-2.0 parts; Corrosion inhibitor, 0.1-0.5 parts; Surfactant, 0.2-0.4 parts; pH adjuster, 0.2-0.3 parts.
[0052] According to one embodiment of the present invention, the abrasive comprises the square cerium oxide composite material as described in the first aspect of the embodiment.
[0053] According to one embodiment of the present invention, the oxidant includes potassium permanganate and / or hydrogen peroxide. The oxidant can promote chemical reactions and accelerate material removal.
[0054] According to one embodiment of the present invention, the complexing agent includes glutamic acid and / or acetylamino acid. The complexing agent can form a complex to stabilize the metal ions in the solution and prevent them from precipitation.
[0055] According to one embodiment of the present invention, the corrosion inhibitor includes ammonia water. The corrosion inhibitor can reduce corrosion of areas that do not require polishing and protect the surface of the material.
[0056] According to one embodiment of the present invention, the surfactant includes polyacrylate ether. The surfactant can reduce surface tension and improve the wettability and dispersibility of the polishing liquid.
[0057] According to one embodiment of the present invention, the pH regulator includes citrate. The pH regulator can adjust the pH value of the solution and optimize the chemical reaction conditions during the polishing process.
[0058] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be obvious from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 This is a flow chart for preparing spherical composite cerium oxide in Example 1.
[0060] Figure 2 This is the SEM image of the spherical composite cerium oxide prepared in Example 1. DETAILED DESCRIPTION
[0061] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0062] The words "preferred", "more preferred" and the like in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0063] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0064] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.
[0065] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0066] Example 1 A spherical composite cerium oxide, the preparation raw materials include the following components: Cerium source; Praseodymium source; Neodymium salts; ammonia; Ammonium source; Organic acids; nitric acid; water; The cerium source is cerium nitrate; The above-mentioned ammonium source is ammonium nitrate; The above organic acid is acetic acid; The praseodymium source is praseodymium nitrate; The above-mentioned neodymium salt is neodymium nitrate.
[0067] Preparation of the above spherical composite cerium oxide, the flow chart is as follows Figure 1 The SEM image of the prepared spherical composite cerium oxide is shown in Figure 2 Specifically, the following steps are included: A1: dissolving an ammonium source in water, then adding a praseodymium source and a neodymium salt and stirring until a transparent and clear solution is obtained, wherein the molar ratio of cerium ions, praseodymium ions and neodymium ions in the cerium source, the praseodymium source and the neodymium salt is 80000:1:1, and the mass ratio of the ammonium source to water is 1:200; then adding nitric acid and acetic acid in sequence and stirring until a transparent and clear solution is obtained to obtain a first mixed solution, wherein the volume ratio of nitric acid, acetic acid and water is 2:1:200; A2: adding ammonia water and an ammonium source to the first mixed solution, reacting at 85.0°C and 20 MPa high pressure for 60 hours to obtain a second mixed solution; wherein the mass ratio of water in step A1 to the ammonia water and the ammonium source in step A2 is 85:4:2, and the molar ratio of ammonia water and the ammonium source is 1:0.21; A3: adjusting the pH of the second mixed solution to 10.0 to obtain colloidal spherical cerium dioxide, concentrating the cerium dioxide to a concentration of 5% w / w at a high temperature of 120° C. under reduced pressure to obtain colloidal spherical cerium dioxide with a particle size of 80-100 nm; A4 The colloidal spherical cerium dioxide was concentrated under high pressure at 145°C to a solid content of 95.0% w / w, and then centrifuged to obtain a precipitate. The precipitate was dried at 300°C for 8 hours, and after deagglomeration, a nano-spherical composite cerium oxide powder with a D50 of 90±10nm was obtained, with a yield of >99% and a total metal impurity content of <1 ppm.
[0068] Example 2 The difference between Example 2 and Example 1 is that in Example 2, the prepared raw materials do not contain praseodymium source and neodymium salt.
[0069] A spherical cerium oxide, the preparation raw materials include the following components: Cerium source; ammonia; Ammonium source; Organic acids; nitric acid; water; The cerium source is cerium nitrate; The above-mentioned ammonium source is ammonium nitrate; The above organic acid is acetic acid.
[0070] The preparation of the spherical composite cerium oxide comprises the following steps: A1: dissolving an ammonium source in water, and then sequentially adding nitric acid and acetic acid and stirring until a transparent and clear solution is obtained to obtain a first mixed solution, wherein the volume ratio of nitric acid, acetic acid and water is 2:1:200; A2: adding ammonia water and an ammonium source to the first mixed solution, reacting at 85.0°C and 20 MPa high pressure for 60 hours to obtain a second mixed solution; wherein the mass ratio of water to ammonia water and the ammonium source is 85:4:2, and the molar ratio of ammonia water and the ammonium source is 1:0.21; A3 adjusting the pH of the second mixed solution to 10.0 to obtain colloidal cerium dioxide, concentrating the cerium dioxide to a concentration of 5% w / w at 120° C. under reduced pressure to obtain colloidal spherical cerium dioxide; A4 The colloidal spherical cerium dioxide was concentrated under high pressure at 145°C to a solid content of 95.0% w / w, and then centrifuged to obtain a precipitate. The precipitate was dried at 300°C for 8 hours, and after deagglomeration, a nano-spherical composite cerium oxide powder with a D50 of 90±30 was obtained, with a yield of 85% and a total metal impurity content of <100ppm.
[0071] Example 3 The difference between Example 3 and Example 1 is that in Example 3, the molar ratio of ammonia water to ammonium source is 1:0.4.
[0072] A spherical composite cerium oxide, the preparation raw materials include the following components: Cerium source; Praseodymium source; Neodymium salts; ammonia; Ammonium source; Organic acids; nitric acid; water; The cerium source is cerium nitrate; The above-mentioned ammonium source is ammonium nitrate; The above organic acid is acetic acid; The praseodymium source is praseodymium nitrate; The above-mentioned neodymium salt is neodymium nitrate.
[0073] The preparation of the spherical composite cerium oxide comprises the following steps: A1: dissolving an ammonium source in water, then adding a praseodymium source and a neodymium salt and stirring until a transparent and clear solution is obtained, wherein the molar ratio of cerium ions to praseodymium ions and neodymium ions in the cerium source, the praseodymium source and the neodymium salt is 80000:1:1, and the mass ratio of the ammonium source to water is 1:200; then adding nitric acid and acetic acid in sequence and stirring until a transparent and clear solution is obtained to obtain a first mixed solution, wherein the volume ratio of nitric acid, acetic acid and water is 2:1:200; A2: adding ammonia water and an ammonium source to the first mixed solution, reacting at 85.0°C and 20 MPa high pressure for 60 hours to obtain a second mixed solution; wherein the mass ratio of water to ammonia water and the ammonium source is 85:4:2, and the molar ratio of ammonia water and the ammonium source is 1:0.4; A3 adjusting the pH of the second mixed solution to 10.0 to obtain colloidal spherical cerium dioxide, concentrating the cerium dioxide concentration to 5% w / w at 120° C. under reduced pressure to obtain colloidal spherical cerium dioxide; A4 The colloidal spherical cerium dioxide was concentrated under high pressure at 145°C to a solid content of 95.0% w / w, and then centrifuged to obtain a precipitate. The precipitate was dried at 300°C for 8 hours, and after deagglomeration, a nano-spherical composite cerium oxide powder with a D50 of 90±70nm was obtained, with a yield of 81% and an impurity content of <100ppm.
[0074] Example 4 A polishing liquid having the following components in parts by weight: Abrasive, 1.5 parts; Ultrapure water, 85.0 parts; Oxidant, 0.5 part; Complexing agent, 1.0 part; Corrosion inhibitor, 0.1 part; Surfactant, 0.2 parts; pH adjuster, 0.2 parts.
[0075] The abrasive is the nano-spherical composite cerium oxide powder prepared in Example 1; Wherein, the oxidant is potassium permanganate; Wherein, the complexing agent is glutamic acid; Wherein, the corrosion inhibitor is ammonia water; Wherein, the surfactant is polyacrylate; Wherein, the pH adjuster is citrate.
[0076] Example 5 A method for semiconductor polishing using the polishing liquid of Example 4 comprises the following steps: Check the polishing pads, polishing discs and other components of the CMP equipment to ensure they are clean and functioning properly; Fix the silicon wafer to be polished on the polishing plate to ensure it is firm; Start the equipment, spray the polishing liquid evenly onto the surface of the polishing pad, and start the polishing process; After polishing, use deionized water to thoroughly clean the surface of the silicon wafer to remove residual polishing liquid; Use nitrogen to dry the wafer to prevent water stains.
[0077] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the molar ratio of cerium ions to praseodymium ions and neodymium ions in the cerium source, praseodymium source and neodymium salt is 10:1:1.
[0078] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, the mass ratio of the ammonium source to water is 1:30000.
[0079] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, the mass ratio of the ammonium source to water is 1:50.
[0080] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that in step A1 of Comparative Example 4, acetic acid is added first and then nitric acid.
[0081] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that in step A1 of Comparative Example 5, only nitric acid is added without acetic acid.
[0082] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that in step A1 of Comparative Example 6, only acetic acid is added without nitric acid.
[0083] Comparative Example 7 The difference between Comparative Example 7 and Example 1 is that in Comparative Example 7, the volume ratio of nitric acid, acetic acid and water is 2:1:75.
[0084] Comparative Example 8 The difference between Comparative Example 8 and Example 1 is that the volume ratio of nitric acid, acetic acid and water in Comparative Example 8 is 2:1:300.
[0085] Comparative Example 9 The difference between Comparative Example 9 and Example 1 is that in step A2 of Comparative Example 9, no ammonia water is added.
[0086] Comparative Example 10 The difference between Comparative Example 10 and Example 1 is that in step A2 of Comparative Example 10, no ammonium source is added.
[0087] Comparative Example 11 The difference between Comparative Example 11 and Example 1 is that in step A2 of Comparative Example 11, the mass ratio of water to ammonia water and ammonium source is 40:4:2.
[0088] Comparative Example 12 The difference between Comparative Example 12 and Example 1 is that in step A2 of Comparative Example 12, the mass ratio of water to ammonia water and ammonium source is 120:4:2.
[0089] Comparative Example 13 The difference between Comparative Example 13 and Example 1 is that the molar ratio of ammonia water to ammonium source in step A2 of Comparative Example 13 is 1:0.005.
[0090] Comparative Example 14 The difference between Comparative Example 14 and Example 1 is that in step A2 of Comparative Example 14, the reaction temperature is 15.0°C.
[0091] Comparative Example 15 The difference between Comparative Example 15 and Example 1 is that in step A2 of Comparative Example 15, the reaction temperature is 170.0°C.
[0092] Comparative Example 16 The difference between Comparative Example 16 and Example 1 is that in step A2 of Comparative Example 16, the reaction time is 50 minutes.
[0093] Comparative Example 17 The difference between Comparative Example 17 and Example 1 is that in step A2 of Comparative Example 17, the reaction time is 120 hours.
[0094] Comparative Example 18 The difference between Comparative Example 18 and Example 1 is that in step A3 of Comparative Example 18, the pH is adjusted to 6.0.
[0095] Comparative Example 19 The difference between Comparative Example 19 and Example 1 is that in step A3 of Comparative Example 19, the concentrated product is concentrated under reduced pressure at 60° C. The temperature is too low and the concentrated product cannot be concentrated.
[0096] Comparative Example 20 The difference between Comparative Example 20 and Example 1 is that in step A3 of Comparative Example 20, the concentrated product is concentrated under reduced pressure at 200° C. The temperature is too high, which may cause explosion risk.
[0097] Comparative Example 21 The difference between Comparative Example 21 and Example 1 is that in step A4 of Comparative Example 21, high pressure concentration is performed at 80°C.
[0098] Since the temperature is too low, the concentration cannot reach the specified concentration.
[0099] Comparative Example 22 The difference between Comparative Example 22 and Example 1 is that in step A4 of Comparative Example 22, high pressure concentration is performed at 200°C.
[0100] There is a risk of explosion due to excessive temperature.
[0101] Comparative Example 23 The difference between Comparative Example 23 and Example 1 is that in step A4 of Comparative Example 23, the moisture cannot be completely removed during drying at a temperature of 280°C.
[0102] Comparative Example 24 The difference between Comparative Example 24 and Example 1 is that in step A4 of Comparative Example 24, the morphology of the product nanoparticles is changed by drying at a temperature of 1200° C. and the spherical shape cannot be maintained.
[0103] Comparative Example 25 The difference between Comparative Example 25 and Example 1 is that in step A4 of Comparative Example 25, the drying time is adjusted to 1.5 hours, resulting in the inability to completely remove the moisture.
[0104] Comparative Example 26 The difference between Comparative Example 26 and Example 1 is that in step A4 of Comparative Example 26, the drying time is adjusted to 12 hours, which is too long, wastes energy, and affects the product morphology.
[0105] Performance Test: The cerium oxide composite material powders prepared in Examples 1-3 and Comparative Examples 1-19 were analyzed. The analysis results are shown in Table 1.
[0106] Table 1
[0107] From Table 1, it can be seen that in Comparative Example 1, the amount of praseodymium ions and neodymium ions added relative to cerium ions is too large, resulting in the particles being deformed, the particle size becoming larger, and the amount of impurities also increasing.
[0108] In Example 2, no praseodymium or neodymium is doped, resulting in a significant increase in the impurity content of the product.
[0109] In Example 3, the molar ratio of ammonia water to ammonium source is 1: 0.4. Excessive ammonium source will bring excess metal impurities and also affect the reaction rate. Although the product is still spherical nanocomposite cerium oxide, its impurity content is increased, which does not meet the requirements of semiconductor applications.
[0110] In Comparative Example 2, the mass ratio of the ammonium source to water is too low, resulting in an extremely low reaction rate and poor particle formation.
[0111] In Comparative Example 3, the mass ratio of the ammonium source to water is too high, resulting in an overly fast reaction rate and failure to form spherical nanoparticles.
[0112] Comparative Example 4 changes the order of adding the organic acid and nitric acid, resulting in the reaction not being able to proceed smoothly.
[0113] In Comparative Example 5-6, no organic acid or nitric acid was added, resulting in the reaction not being able to proceed smoothly.
[0114] In Comparative Example 7, the volume ratio of nitric acid, acetic acid and water was changed to 2:1:75, and the amount of water was too little, so the particle shape could not be maintained or even could not be formed.
[0115] In Comparative Example 8, the volume ratio of nitric acid, acetic acid and water was changed to 2:1:300. Too much water was used, resulting in the inability to maintain the particle shape, increased impurities, decreased reaction rate and incomplete reaction.
[0116] In Comparative Examples 9-10, due to the small amount of ammonia water or ammonium source added in step A2, the reaction efficiency decreased, the reaction was incomplete and the particle morphology changed.
[0117] In Comparative Example 11, since the mass ratio of water to ammonia water and ammonium source was changed to 40:4:2 in step A2, the reaction was too intense, resulting in the particles not being formed.
[0118] In Comparative Example 12, since the mass ratio of water to ammonia water and ammonium source was changed to 120:4:2 in step A2, the reaction was too slow, resulting in the yield dropping below 50%.
[0119] In Comparative Example 13, since the molar ratio of ammonia water and ammonium source was changed to 1: 0.005 in step A2, the reaction was too slow, resulting in insufficient reaction and unformed particles.
[0120] In Comparative Example 14, the reaction could not proceed at 15°C.
[0121] In Comparative Example 15, the reaction was carried out at 170° C., which was too high to obtain formed nano-cerium dioxide particles.
[0122] In Comparative Example 16, the raw materials were reacted at 85.0°C and 20 MPa high pressure for 50 minutes. The time was too short and the reaction was insufficient, resulting in a product without a shape.
[0123] In Comparative Example 17, the raw materials were reacted at 85.0°C and 20 MPa high pressure for 120 hours. This time was too long, which not only wasted time, energy and water, but also resulted in the product being unformed.
[0124] In Comparative Example 18, in step A3, the pH was adjusted to 6.0, resulting in a change in the shape of the product nanoparticles.
[0125] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A spherical composite cerium oxide, characterized in that: The raw materials for preparation include the following components: Cerium source; ammonia; Ammonium source; Organic acids; nitric acid; water; The D50 of the spherical composite cerium oxide is 20-160nm; The molar ratio of the ammonia water to the ammonium source is 1:0.2-0.
4.
2. The spherical composite cerium oxide according to claim 1, characterized in that: The raw materials for preparing the spherical composite cerium oxide also include a praseodymium source and / or a neodymium source.
3. The spherical composite cerium oxide according to claim 1, characterized in that: The D50 of the spherical composite cerium oxide is 90±10 nm.
4. A method for preparing a spherical composite cerium oxide as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1: mixing a cerium source with water, nitric acid, and an organic acid in sequence to obtain a first mixed solution; S2 adding ammonia water and an ammonium source to the first mixed solution, heating for reaction, and obtaining a second mixed solution; S3: adjusting the pH of the second mixed solution to be alkaline, and obtaining the spherical composite cerium oxide through a sol-gel reaction; In the step S2, the heating reaction temperature is 30°C-120°C, and the heating reaction time is 1-60 hours.
5. The preparation method according to claim 4, characterized in that: In the step S1, the mass ratio of the cerium source to water is 1:100-20000.
6. The preparation method according to claim 4, characterized in that: In step S1, the volume ratio of nitric acid, organic acid and water is 2:1:100-280.
7. The preparation method according to claim 4, characterized in that: The mass ratio of the water in step S1 to the ammonia water and the ammonium source in step S2 is 50-100:4:
2.
8. A method for preparing a spherical composite cerium oxide as claimed in claim 2, characterized in that: The method comprises the following steps, and further comprises the following steps: A1: mixing a cerium source with water, a praseodymium source and / or a neodymium source, nitric acid, and an organic acid in sequence to obtain a first mixed solution; A2 adds ammonia water and an ammonium source to the first mixed solution, and heats the mixture to react, thereby obtaining a second mixed solution; A3 adjusts the pH of the second mixed solution to be alkaline to obtain colloidal spherical cerium dioxide, and obtains the spherical composite cerium oxide through sol-gel reaction, concentration operation, and centrifugation operation; In the step A2, the heating reaction temperature is 30° C.-120° C., and the heating reaction time is 1-60 hours.
9. A semiconductor polishing material, characterized in that: The spherical cerium oxide composite material comprises the spherical cerium oxide composite material according to any one of claims 1 to 3.
10. A method for polishing a semiconductor, characterized in that: The following steps are involved: The wafer to be polished is fixed on the polishing plate, the polishing equipment is started, the semiconductor polishing material according to claim 9 is prepared into a polishing liquid and then sprayed onto the surface of the polishing pad for polishing.
Citation Information
Patent Citations
Method for preparing nano-Ce-Magnesium coumpoud oxide
CN101036881A
Rare earth polishing powder and production method thereof
CN101899281A
Preparation method of hydrated nano cerium oxide sol
CN101973570A
Method for preparing cerium dioxide material with high specific surface area
CN102923753A
Preparation method of catalyst for catalytic combustion of polycyclic aromatic hydrocarbon
CN107149942A
Cited By
Silicon carbide polishing solution and preparation method thereof
CN122104062A